Films based on bacteriorhodopsin in sol-gel matrices - Korposh, Sergiy; Sichka, M. Y.; Trikur, I. I.; Sharkan, Y. P.; Yang, D. H.; Lee, Seung-Woo; Ramsden, Jeremy J. (International Society for Optical Engineering; 1999, 2005)
The bacteriorhodopsin film in gelatin matrixes which are used as sensitive elements of integrated optic and fibre-optic sensors of various vapor and gases components will not be able to carry out the chemical control of aqueous solutions. In the given paper the results of technological development of obtaining the bacteriorhodopsin (bR) films in a sol-gel matrix are represented. The films are obtained in a broad thickness range (from 0.5 to 20 microns) with various bR concentrations and photosensitize additives. The optimal technological conditions of obtaining of uniform films with given optical parameters are defined. The surface morphology and cross section of the obtained films was studied using an AFM and SEM. The films have a reasonable surface roughness (~ 100 nm) and a uniform distribution of the purple membrane fragments in the nanostructured sol-gel glass matrix along the films surface and thickness. The transmission spectrums have the characteristic for bR the absorption band, the value of which depends on bR concentration and technological features of the films deposition. The investigated photosensitive properties of the obtained films and influence on them of chemical components of aqueous solutions, allow recommending the thin bR films in sol-gel matrixes for creation of planar waveguides in the role of components of the chemical sensors of liquid solutions.